Policy context for the forest in the future: Pandemic, economy and environment in Peru - Iturregui Byrne, Patricia (2020)
How is the national competitiveness plan connected to sustainability in Peru? The OECD recommendations for environmental performance in Peru related to economy and environment has been pursued? How to reverse the Amazon deforestation in Peru according to experts and ex ministers of the Environment? These are the questions that this article aims to answer pointing out which are the areas for future academic research.